Ten-Year Outcomes of 1- and 2-Level Cervical Disc Arthroplasty From the Mobi-C Investigational Device Exemption Clinical Trial. (18th November 2021) - Kim, Kee; Hoffman, Greg; Bae, Hyun; Redmond, Andy; Hisey, Michael; Nunley, Pierce; Jackson, Robert; Tahernia, David; Araghi, Ali
Graphical Abstract: